2017
DOI: 10.1111/anec.12430
|View full text |Cite
|
Sign up to set email alerts
|

Arrhythmic risk stratification in heart failure: Time for the next step?

Abstract: The era of ejection fraction as the sole risk stratifier for arrhythmic risk in heart failure appears to be drawing to an end, especially if current underway large studies validate previous findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…24 The value of SAECG, incorporated in risk-stratification strategies, is further underscored by a recent study 25 Current evidence indicates that multifactorial approaches are also pertinent among DCM patients, encompassing invasive and noninvasive indices. 3 SAECG holds a place in this respect, as shown by early clinical reports, where SAECG could discriminate those DCM patients with a history of VT from those without, 29 albeit with an inferior predictive value compared to MI patients. 30 In keeping with these findings, one-year event-free survival was 95% in a larger cohort of DCM patients with absence of LPs, contrasting the only 39% in patients with an abnormal SAECG 31 ; of note, multivariate analysis in this study demonstrated that SAECG and functional class were independent predictors of survival.…”
Section: Limitations Of Current Algorithmsmentioning
confidence: 92%
See 4 more Smart Citations
“…24 The value of SAECG, incorporated in risk-stratification strategies, is further underscored by a recent study 25 Current evidence indicates that multifactorial approaches are also pertinent among DCM patients, encompassing invasive and noninvasive indices. 3 SAECG holds a place in this respect, as shown by early clinical reports, where SAECG could discriminate those DCM patients with a history of VT from those without, 29 albeit with an inferior predictive value compared to MI patients. 30 In keeping with these findings, one-year event-free survival was 95% in a larger cohort of DCM patients with absence of LPs, contrasting the only 39% in patients with an abnormal SAECG 31 ; of note, multivariate analysis in this study demonstrated that SAECG and functional class were independent predictors of survival.…”
Section: Limitations Of Current Algorithmsmentioning
confidence: 92%
“…Current evidence indicates that multifactorial approaches are also pertinent among DCM patients, encompassing invasive and noninvasive indices . SAECG holds a place in this respect, as shown by early clinical reports, where SAECG could discriminate those DCM patients with a history of VT from those without, albeit with an inferior predictive value compared to MI patients .…”
Section: Dilated and Right Ventricular Cardiomyopathiesmentioning
confidence: 98%
See 3 more Smart Citations